(untitled) (Journal Of Educational and Psychological Researches, 2017)
Represents the individual’s sense of responsibility in various forms, important for personal normal traits, whether the responsibility towards the family, or the institution in which it operates, or about colleagues and friends and neighbors and other people who mingle with them, or about society in general, or about humanity as a whole, though the hair everyone in the community of responsibility towards other people who are assigned to care for them and take care of them, and some noticeable work that people anywhere if Have the social responsibility, and stressed in their actions to the general principles of such cooperation, sacrifice and altruism and love and helping others, and if it prevailed in such behaviors, it will be reflected on the nature of society and the degree of stability, but if there was the contrary, this society, will suffer from the sharp deterioration of the divisions in the community structure, and that it was up as well as to what is going through this community of force majeure, both politically and economically and which affects the social offender where and Kdaany Iraqi society from multiple problems, led to the lack of political and social stability, and therefore, the loss of a sense of belonging to the homeland and social integration with the community leads to the direction of the individual to the narrow tribal loyalties, tribal, sectarian and nationalist ( al-Jubouri, 2009:55 ) Thus, the verification of the above case is a problem that tries to look her studies by identifying the relationship between citizenship and social responsibility among university students Research Goals aims to identify research: 1- citizenship among university students 2- social responsibility among university students 3- relationship between citizenship and social responsibility among university students In order to achieve the goals of current research, the researcher building Standart citizenship and social responsibility in accordance with the view adopted in this research has citizenship measure be 30 paragraph Lama social responsibility scale may be a 35-paragraph has been checked reliability and validity of scales and then it has been applied to a sample search (400) students have reached the current search: 1-The research sample have a sense of belonging and ensuring the country succumbed to the circumstances faced by the country. 2- that Aebenh current research have high sense of social responsibility. 3-azart results that there is a link between citizenship and social responsibility as it can be explained by a sense of belonging, which is a key indication for citizenship as well as the sense of duty towards society